2015
DOI: 10.17123/atad.vol26iss225595
|View full text |Cite
|
Sign up to set email alerts
|

Uygulamada Menü Analizi Nasıl Yapılmaktadır? Beş Yıldızlı Otellerin Mutfak Şeflerinin Görüşleri

Abstract: Menü analizi menü yönetiminin en önemli araçlarından biri olarak kabul edilmektedir (Özdemir ve Çalışkan 2013). Menü analizinin içeriği iki temel boyuttan oluşmaktadır. İlk olarak menüde yer alan her bir menü kaleminin performansı yönetim tarafından belirlenen performans göstergeleri açısından değerlendirilmektedir (Çalışkan ve Özdemir 2011). Ardından beklenenin altında performans gösteren menü kalemleri için iyileştirme çalışmaları yapılmaktadır (Jones ve Mifli 2001).Akademik açıdan bakıldığında ise menülerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
(10 reference statements)
0
5
0
5
Order By: Relevance
“…These findings are similar to Kwong (2005), who found that Asian restaurant operators perform menu analysis based on past experience and intuition. Özdemir & Nebioğlu (2015) also reported that five-star hotel chefs used similar strategies. In short, intuitive approaches to menu analysis remain prominent.…”
Section: Theoretical Implicationsmentioning
confidence: 87%
See 2 more Smart Citations
“…These findings are similar to Kwong (2005), who found that Asian restaurant operators perform menu analysis based on past experience and intuition. Özdemir & Nebioğlu (2015) also reported that five-star hotel chefs used similar strategies. In short, intuitive approaches to menu analysis remain prominent.…”
Section: Theoretical Implicationsmentioning
confidence: 87%
“…Menu analysis, which is the fourth area, measures menu performance (Özdemir & Nebioğlu, 2015). It has become prominent since the 1980s.…”
Section: Studies On Menu Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Graneheim and Lundman (2004), Elo and Kyngas (2008) and Hsieh and Shannon (2005) state that researchers can use several different methods to prove the reliability of their content analysis. In this way, the reader can understand exactly what stages the research went through and how it took shape (Ö zdemir and Nebio glu, 2015). For this reason, detailed information was tried to be given about the research method and stages used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Finansal ve Finansal Olmayan Verilerle Menü Performansının Değerlendirilmesinında yaptıkları bir çalışmada, tabak artık verilerinin (dolayısıyla tabak tüketiminin) menü değerlendirme sürecinde etkili bir şekilde kullanılabileceğini ileri sürmüştür. Nitekim yakın bir geçmişte beş yıldızlı otel işletmelerinde çalışan mutfak şefleri örnekleminde yapılmış bir araştırmada, tabak artıklarının öznel olarak menü analiz sürecinde dikkate alındığı ortaya koyulmuştur(Özdemir ve Nebioğlu 2015).…”
unclassified